2021
DOI: 10.1186/s12879-021-06106-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic urinary tract infections and associated risk factors in Pakistani Muslim type 2 diabetic patients

Abstract: Background One of the leading long-term complications of type 2 diabetes mellitus (T2DM) includes renal dysfunction and urinary tract infections (UTI) which are considered to be prevalent in uncontrolled diabetes. Moreover, physiological factors like age, gender, duration of diabetes, other diabetic complications like neuropathy, autonomic neuropathy and glycosuria are also considered as predisposing factors for increased prevalence of UTI in diabetes which can be symptomatic or asymptomatic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
5
11
0
Order By: Relevance
“…Another paramount concern in patients with T2DM is UTI that warrants a routine urine analysis. It was established that patients with T2DM more than 40 years of age and female patients in particular are at a higher risk of asymptomatic UTI, although the overall prevalence of UTI in T2DM is nearly 11.5% [35] [36] [37] [38]. A retrospective analysis of tofogliflozin, an SGLT2 inhibitor, exhibited significant glucose-lowering competencies with low associated risk of electrolyte abnormalities and dehydration [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another paramount concern in patients with T2DM is UTI that warrants a routine urine analysis. It was established that patients with T2DM more than 40 years of age and female patients in particular are at a higher risk of asymptomatic UTI, although the overall prevalence of UTI in T2DM is nearly 11.5% [35] [36] [37] [38]. A retrospective analysis of tofogliflozin, an SGLT2 inhibitor, exhibited significant glucose-lowering competencies with low associated risk of electrolyte abnormalities and dehydration [39].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, 8% to 26% of asymptomatic bacteriuria have been observed in diabetic women with a projected incidence of 2 to 3 times higher than non-diabetic women. 13 A cohort study was conducted for over 6000 patients with diabetes mellitus registered for 10 clinical trials of diabetes therapies. The prevalence of urine infection was found to be 91.5/1000 for women and 28.2/1000 for men, with the cumulative risk of 3.5% and 1.1%, respectively in females and males over 6 months period.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with adequate glycaemic control, only 3 (15.79%) incidences of UTI were discovered. 9,19 Among gram positive, Enterococcus represented 6.2% of isolated pathogens further more Staphylococcus aureus 3.2% was found in few cases at most 1% specimens exist to Candida species. Gram-negative infections reveal disturbing resistant to first and second-line agents Ampicillin, Fluroquinolones, Trimethoprim/sulfamethoxazole, Amoxicillin, in this investigation.…”
Section: Discussionmentioning
confidence: 99%